2018
DOI: 10.1039/c8sc01262h
|View full text |Cite
|
Sign up to set email alerts
|

Conformational landscape of the epidermal growth factor receptor kinase reveals a mutant specific allosteric pocket

Abstract: An oncogenic mutant-specific druggable allosteric pocket captured by MD simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 33 publications
0
25
2
Order By: Relevance
“…We focused on all diverse acquired mutations at the binding sites, exploring the binding site flexibility of EGFR kinase domains with the del746-750/T790M/C797S/ mutation and the L858R/T790M/C797S mutations by using µs-scale molecular dynamics (MD). MD simulation has been successfully applied to study the EGFR conformation space at a computational physiological environment [21][22][23][24] . For example, Park et.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on all diverse acquired mutations at the binding sites, exploring the binding site flexibility of EGFR kinase domains with the del746-750/T790M/C797S/ mutation and the L858R/T790M/C797S mutations by using µs-scale molecular dynamics (MD). MD simulation has been successfully applied to study the EGFR conformation space at a computational physiological environment [21][22][23][24] . For example, Park et.…”
Section: Introductionmentioning
confidence: 99%
“…The findings suggested that, in combination with anti-EGFR antibodies such as cetuximab, 4th generation inhibitors could overcome resistance to the triple L834R/T766M/C773 mutation, which is resistant to all current EGFR-targeted therapies. Recent MD simulations have investigated the structural basis underlying the binding of 4th generation inhibitors [167]. The results revealed that the conformational destabilization of the short helix that carries Leu834 in the wild type exposes the allosteric pocket, which is otherwise occluded by a set of sidechains including L834.…”
Section: Kinase Domain Conformations and Their Coupling To Tyrosinmentioning
confidence: 99%
“…As one of the most efficient and precise paradigms to tweak proteins’ functional activity and an important supplement to the traditional orthosteric-targeting strategy, allosteric modulators by targeting allosteric sites have enhanced specificity and reduced adverse effects, thereby presenting a promising avenue for modern drug development [ 4 , 5 , 6 ]. The latest decade has witnessed the upsurge of structural biology and protein allostery research, which led to inspiring success in allosteric drug discovery throughout an extended list of critical therapeutic targets such as kinases [ 7 , 8 , 9 ], Ras [ 10 , 11 , 12 , 13 , 14 ], and G-protein-coupled receptors [ 15 , 16 ], proving the enormous potential of allosteric regulation.…”
Section: Introductionmentioning
confidence: 99%